Seven dimensions of sexual music: Monodic and dyadic sexual behavior in couples - Pereyra Quiñones, José Luis (2023)
The intimate sexual behavior of couples (normal or non-pathological) must be described by psychologists, for this they use two perspectives; one is the first a) psychopathology of the DSM 5 and ICD-10 or, the second b) the perspective of positive psychology, which uses the models of Kinsey (1953), Masters and Johnson (1966), Kaplan (1979), Schnarch (1991), Whipple and Brash-Mc.Greer (1997), and Basson (2000). A panel of experts sought to validate a new taxonomy of erotic behaviors. Sexual music refers to the individual and dyadic behavior that a couple does to reach sexual intercourse; the qualities of the monodic behavior of a lover are: a) Intensity, b) Duration, c) Timbre and d) Sexual tone; and the dyadic musical coordination of two lovers are: x) Rhythm, y) Melody and z) Sexual harmony. A panel of seven experts using the Delphi method validated the content of the seven dimensions theory of sexual music (Pereyra, 2020) providing the conceptual definition and operationalization of the sexual variables used; In addition, the experts provided the clinical casuistry of their particular cases.